A Global Survey of Carbohydrate Esterase Families 1 and 10 in Oomycetes - de Vries, Sophie; de Vries, Jan (Frontiers in Genetics, 2020)
Carbohydrate-active enzymes (CAZymes) are a cornerstone in the phytopathogenicity of filamentous microbes. CAZymes are required for every step of a successful infection cycle—from penetration, to nutrient acquisition (during colonization), to exit and dispersal. Yet, CAZymes are not a unique feature of filamentous pathogens. They are found across eukaryotic genomes and including, for example, saprotrophic relatives of major pathogens. Comparative genomics and functional analyses revealed that CAZyme content is shaped by a multitude of factors, including utilized substrate, lifestyle, and host preference. Yet, family size alone says little about usage. Indeed, in a previous study we found that CAZymes encoded by the gene family CE1 and the putative CAZymes of the family CE10, while not specifically enriched in number, were suggested to have lifestyle-specific gene expression patterns. Here, we used comparative genomics and a clustering approach to understand how the repertoire of the CE1 and CE10-encoding gene families is shaped across oomycete evolution. These data are combined with comparative transcriptomic analyses across homologous clusters within the gene families. We find that CE1 and CE10 have been reduced in number in biotrophic oomycetes independent of the phylogenetic relationship of the biotrophs to each other. The reduction in CE1 is different from that observed for CE10: While in CE10 specific clusters of homologous sequences show convergent reduction, CE1 reduction is caused by species-specific losses. Comparative transcriptomics revealed that some clusters of CE1 or CE10 sequences have a higher expression than others, independent of the species composition within them. Further, we find that CE1 and CE10-encoding genes are mainly induced in plant pathogens and that some homologous genes show lifestyle-specific gene expression levels during infection, with hemibiotrophs showing the highest expression levels.